Is selenium status associated with mortality risk in hemodialysis patients? - Milena B Stockler-Pinto; Luis Guillermo C Velarde; Denise Mafra (The Korean Society of Nephrology, 2012)
Previous studies have indicated selenium (Se) deficiency in hemodialysis (HD) patients and it may increase the mortality risk for death among hemodialysis patients. Studies from our laboratory showed poor nutritional status of Se in HD patients. The purpose of this study was to evaluate Se levels as predictors of cardiovascular mortality in HD patients. A total of 44 HD patients (53.0±15.0 years old, average time on dialysis 80.1±112.7 months, BMI, 24.6±34.3 kg/m2) from the RenalCor Clinic in Rio de Janeiro, Brazil, were followed up 36 months. The plasma and erythrocyte Se levels were determined by atomic absorption spectrophotometry with hydride generation (Hitachi, Z−500). Associations between Se levels and cardiovascular mortality in HD patients were examined by Cox's regression model. Mean plasma Se was 72.1±70.1 μg/L and erythrocyte Se 194.8±148.91 μg/L and a total of 17 patients died from cardiovascular event during the follow-up period. Analysis by the Cox model showed that only low erythrocyte Se levels were significant predictors of mortality (hazard ratio [HR] 0.995 [95% CI 0.991-0.999]. In conclusion, decreased erythrocyte Se level may increase the risk of death in hemodialysis patients.